Determinan Struktur Modal: Perspektif Pecking Order Theory dan Trade-off Theory - Ariawan Ariawan; Eka Zahra Solikahan (Journal of Technopreneurship on Economics and Business Review, 2022)
This study aims to determine how much influence the asset structure, non-debt tax shields, firm size and profitability have on the capital structure of the Food and Baverages Sub-Sector Companies listed on the Indonesia Stock Exchange. The method used in this study is a quantitative method. The data analysis technique used in this research is multiple regression analysis. Asset structure has a positive and significant impact on the capital structure of companies listed in the Food and Beverage Industry Sector on the IDX for the 2014-2018 period. With the value of the beta coefficient included in the low category, the results of this study are in accordance with the Trade-off theory. Non-debt tax shields have no significant effect on the capital structure of companies listed in the Food and Beverage Industry Sector on the IDX for the 2014-2018 period. With the value of the beta coefficient being very low, the results of this study are not in accordance with the trade-off theory. Firm size has a significant effect on the capital structure of companies listed in the Food and Beverage Industry Sector on the IDX for the 2014-2018 period. With a low beta coefficient value. The results of this study are not in accordance with the pecking order theory. Profitability has a positive and significant effect on the capital structure of companies in the Food and Beverage Industry Sector Listing on the IDX for the 2014-2018 period. With the value of the beta coefficient is included in the low category. The results of this study are in accordance with the pecking order theory.